The antecedents and outcomes of workplace ostracism: A meta-analysis. - Howard, Matt C.; Cogswell, Joshua E.; Smith, Mickey B. (Journal of Applied Psychology, 2020)
Researchers have shown great interest in the antecedents and outcomes of workplace ostracism, which has led to an expansive body of research. In light of this work, the current article fulfills the need for a comprehensive review and meta-analysis of the antecedents and outcomes associated with workplace ostracism. We begin our review by adapting a victimization perspective to understand ostracism as a triadic social process between the victim, perpetrator, and the environment. The meta-analytic results then support that leadership characteristics are the strongest related antecedents of workplace ostracism, followed by certain aspects of personality (e.g., Big Five) and contextual characteristics (e.g., social support). The results also show that workplace ostracism very strongly relates to deviance, and it strongly relates to other performance outcomes (e.g., core-performance, helping, voice), well-being outcomes (e.g., psychological well-being, emotions, self-perceptions), and organizational perceptions (e.g., job satisfaction, commitment, justice). We also show that the relationship of performance, well-being, emotions, and self-perceptions when measured after ostracism was comparable to their relationship when measured before ostracism. These results suggest that the outcomes of ostracism are less certain than previously thought, as they may instead be antecedents of ostracism. Finally, we call for future research to investigate this notion, along with further integration of the victimization perspective as well as the study of contextual predictors and moderators. (PsycInfo Database Record (c) 2020 APA, all rights reserved).